The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.adolescence.2016.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of peers in services for youth with emotional and behavioral challenges: A scoping review

Abstract: This scoping review synthesizes published and unpublished information on Youth Peer Support Services (YPSS), where young adults with current or prior mental health challenges provide support services to other youth and young adults currently struggling with similar difficulties. Existing published and unpublished "grey" literature were reviewed, yielding 30 programs included for data extraction and qualitative syntheses using a descriptive analytic framework. Findings identify variations in service delivery st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
86
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(90 citation statements)
references
References 28 publications
4
86
0
Order By: Relevance
“…Young people also appreciated services that were staffed by young people, and although peer support (ie, young people working as support workers) was less common, youth participation more generally was reported in just over half of the services. Youth participation has been described as a critical ingredient for integrated youth health care services, 7 , 31 , 97 , 98 and, consistent with the literature, was highly valued by young people.…”
Section: Discussionmentioning
confidence: 99%
“…Young people also appreciated services that were staffed by young people, and although peer support (ie, young people working as support workers) was less common, youth participation more generally was reported in just over half of the services. Youth participation has been described as a critical ingredient for integrated youth health care services, 7 , 31 , 97 , 98 and, consistent with the literature, was highly valued by young people.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is now guidance for how to set up peer work programmes in general (Centre of Excellence in Peer Support, ), there is little to guide the development and implementation of youth specific peer work programmes. What is known from a recent scoping review of this area (Gopalan et al, ) demonstrates that there is a need to better describe and evaluate critical factors such as core competencies, training and supervision needs to better define the diverse roles that youth peer workers may play in a range of settings. Despite the use of targeted strategies to integrate the peer workforce in the service, peer workers experienced role confusion and remained uncertain of their role, responsibilities and how to approach their work.…”
Section: Discussionmentioning
confidence: 99%
“…One recent exception to this is a review of youth peer workers in the United States that demonstrated the recent growth and increasing breadth and diversity of youth peer roles (Gopalan, Lee, Harris, Acri, & Munson, ). The review included initiatives that were “peer‐supported,” “partially peer‐delivered” and “peer‐delivered,” operating within and beyond the mental healthcare system for young people aged 9 to 26 years, with youth peer workers aged 9 to 25 years.…”
Section: Introductionmentioning
confidence: 99%
“…The participating organizations are engaged in initiatives to develop clear role descriptions, practice standards, and training activities for peer providers guided by research such as that by Gopalan and associates. 8 Additionally, the current survey findings are being used to guide the development of accessible online training materials focused on identified areas of training need for transition service providers generally.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, youth peer support has increasingly become an integral part of the behavioral health system across the United States. 8 Peer support is characterized as a mutually supportive relationship between people with shared experiences with mental health challenges that may be informal or naturally occurring, or may involve a more formalized relationship in which the individuals offering peer-to-peer support are paid for their services. 9 Young adults entering the workforce as peer support providers bring an array of additional training needs to their work.…”
mentioning
confidence: 99%